2021
DOI: 10.29036/jots.v12i22.253
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Travel Motivations of Domestic Tourists

Abstract: Domestic tourism plays an essential role in the tourism industry and contributes to the overall economic development. This study aims to investigate the relationship between push and pull travel motivations of domestic tourists, their behavioral intentions, a direct influence of travel motivations on perceived benefit and perceived value of domestic tourists. The paper applies the concept of push and pull factors of travel motivation, perceived benefit, perceived value, and behavioral intention. The study impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 53 publications
2
18
1
Order By: Relevance
“…On the other hand, socialization was not statistically significant in influencing domestic tourism performance. These findings were concordant with those of Luvsandavaajav &Narantuya, 2021 andMapingure et al, 2019, where domestic tourists were pushed by the desire for novelty, nature seeking, as well as the need to relax and escape daily routine. Meanwhile, these results differed with those of Subadra et al, (2019) in Bali and Mapingure et al, (2019) in Zimbabwe, who reported that the desire to escape daily routine and prestige were not perceived as important push factors.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…On the other hand, socialization was not statistically significant in influencing domestic tourism performance. These findings were concordant with those of Luvsandavaajav &Narantuya, 2021 andMapingure et al, 2019, where domestic tourists were pushed by the desire for novelty, nature seeking, as well as the need to relax and escape daily routine. Meanwhile, these results differed with those of Subadra et al, (2019) in Bali and Mapingure et al, (2019) in Zimbabwe, who reported that the desire to escape daily routine and prestige were not perceived as important push factors.…”
Section: Discussionsupporting
confidence: 88%
“…These results were consistence with those of a study conducted in Mongolia, where a number of related factors such as the presence of natural scenery, sightseeing, diverse attractions (i.e. cultural, sporting and entertainment); wide open space and good natural atmosphere pulled domestic tourists to destinations (Luvsandavaajav & Narantuya, 2021). Similarly, in Bali and Ladakh, tourists are attracted to the destination by factors ranging from natural attractions, the atmosphere and climate, security/safety and hygiene and an opportunity for outdoor activities (Antara & Prameswari, 2018;V.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations